A six-compound, high performance gasoline surrogate for internal combustion engines: Experimental and numerical study of autoignition using high-pressure shock tubes. (1st February 2020) - Cancino, L.R.; da Silva, A.; De Toni, A.R.; Fikri, M.; Oliveira, A.A.M.; Schulz, C.; Curran, H.J.
Abstract: This paper presents experimental and modeling data for the autoignition of a novel, six-component, high performance gasoline surrogate fuel comprising ethanol, n -heptane, i -octane, 1-hexene, methylcyclohexane, and toluene (AL-P-I-O-N-A). Experimental tests are conducted in two high-pressure shock tubes to determine the ignition delay time as a function of pressure, temperature and equivalence ratio. Ignition delay times were measured at 10 and 30 bar in the temperature range from 749 to 1204 K and equivalence ratios ranging from 0.35 to 1.30 . A modified Arrhenius equation is defined to mathematically describe the ignition delay time of the proposed surrogate. For experimental data with temperatures higher than 900 K, a multiple linear regression identified the pressure dependence exponent of 0.72 and stoichiometry dependence exponent of 0.62, as well as a global activation energy of ≈ 109 kJ/mol. A simplistic approach to mechanism reduction based on the elimination of reactions with no relevant rate of progress was used in order to reduce an extensive detailed kinetics model (hierarchically constructed with more than 17800 reactions). The reduced detailed kinetics model with 4885 elementary reactions among 326 chemical species was used for numerical simulations. Comparisons between the experimental and numerical data are favorable, with the predictions using the reduced kinetics model differing by less than 0.056% when compared to the complete mechanism. It was observed that for low temperatures the proposed reduced kinetics model agrees only qualitatively with the measurements. In order to understand the likely cause of this discrepancy a brute force sensitivity analysis on IDT was performed, elucidating the more influencing reactions on the ignition delay times. The experimental data obtained in this research was compared to available data in the literature in terms of anti-knock index (AKI) and for a scaled pressure of 30 bar ( τ 30 ) at a stoichiometric composition. A modified Arrhenius equation was then fitted and an AKI dependence exponent of - 1.11 was obtained, inferring that the higher the AKI the higher the IDT, independent of fuel composition at temperatures lower than the NTC region. This trend should be confirmed by further studies.